2019
DOI: 10.3390/app9122463
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Banned Veterinary Drugs and Quinolone Residues in Shrimp through Liquid Chromatography–Tandem Mass Spectrometry

Abstract: The presence of antibiotic residues in seafood and their effect on public health constitute a matter of concern for consumers worldwide. Antibiotic residues can have adverse effects on both humans and animals, especially residues of banned veterinary drugs. In this study, we applied a validated method to analyze veterinary drug residues in shrimp, including the levels of banned chloramphenicol, malachite green, leucomalachite green, and four nitrofuran metabolites as well as thiamphenicol, florfenicol, and fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Here, we adopted the analytical approach for sulfonamide residues suggested by the TFDA [16] and that for organophosphorus insecticide residues developed by the European Committee for Standardization, the QuEChERS (quick, easy, cheap, effective, rugged, and safe) method [4,21]-both of which are suitable for detecting trace chemical residues. For the validation of its analytic method, the TFDA [2,22] recommends an acceptable recovery rate of 70-120% [relative standard deviation (RSD) < 15%], 70-120% (RSD < 20%), and 50-125% (RSD < 35%) for chemical residues in food matrices detected in the 0.1-1, 0.001-0.01, and <0.001 mg/kg ranges, respectively. In this study, residues of sulfonamides and organophosphorus insecticides that were identified within the 0.01-0.1 mg/kg ranges were noted to exhibit a recovery rate of 90-120% (RSD < 15%) and 80-120% (RSD < 15%), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we adopted the analytical approach for sulfonamide residues suggested by the TFDA [16] and that for organophosphorus insecticide residues developed by the European Committee for Standardization, the QuEChERS (quick, easy, cheap, effective, rugged, and safe) method [4,21]-both of which are suitable for detecting trace chemical residues. For the validation of its analytic method, the TFDA [2,22] recommends an acceptable recovery rate of 70-120% [relative standard deviation (RSD) < 15%], 70-120% (RSD < 20%), and 50-125% (RSD < 35%) for chemical residues in food matrices detected in the 0.1-1, 0.001-0.01, and <0.001 mg/kg ranges, respectively. In this study, residues of sulfonamides and organophosphorus insecticides that were identified within the 0.01-0.1 mg/kg ranges were noted to exhibit a recovery rate of 90-120% (RSD < 15%) and 80-120% (RSD < 15%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, excessively applying these drugs could result in the cultured organisms retaining drug residues at harvest, potentially exposing consumers to substances toxic for human consumption [2]. We previously detected chloramphenicol in hard clam [6] and shrimp [2] and quinolones in shrimp [2] aquafarms in Taiwan. Moreover, these aquafarms use several insecticides to control ectoparasites and endoparasite growth [7] and several pesticides to limit the growth of aquatic weeds in bodies that include canals, fishponds, and lakes [6].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations